The Ratio of the Genome Two Functional Parts Activity as the Prime Cause of Aging - Salnikov, Lev; Baramiya, Mamuka G. (Frontiers in Aging, 2020)
The metazoans genome contains two functionally independent parts. These are genes that provide for the internal needs of the cell - housekeeping genes(HG)and genes that provide integrative functions and form the body as an integrated whole (IntG). The main paradigm for multicellularity development which has been improved in evolution, is the submission of the autonomy of the body's constituent parts to the interests of the integrated whole. Permanent increase of the "functional tax" of IntG-genome (IntG-shift) and epigenetic restriction of autonomy in phylogenesis and ontogenesis is the essence and root cause of aging, inherent in the very nature of highly integrated multicellularity. Here we propose the criterion for measuring the functional and biological age of cells and the body as a whole based on the IntG/HG ratio and criteria for assessing the effectiveness of any type of palliative geroprotective or radical anti-aging intervention.